Distribution of trichinellosis in Priamurye - I. A. Samsonenko; T. I. Trukhina; V. A. Ryabukha (Российский паразитологический журнал, 2016)
Trichinellosis in the Amur and Khabarovsk region is widespread distributed. During 12 years two species of the domestic and seven species of wild animals became a source of infection of people. Domestic animals were the cause of infection of people in 50 % of cases